Novel splicing‐site mutation in DCAF17 gene causing Woodhouse‐Sakati syndrome in a large consanguineous family. Issue 1 (8th December 2021) - Fozia, Fozia; Shah, Khadim; Nazli, Rubina; Khan, Sher Alam; Ahmad, Ijaz; Mohammad, Noor; Khan, Saadullah; Alotaibi, Amal
Abstract: Background: Woodhouse‐Sakati syndrome is a rare autosomal recessive disease with endocrine and neuroectodermal aberrations with heterogeneous phenotypes and disease course. The most common phenotypes of the disease are progressive sensorineural hearing loss and alopecia, mild‐to‐moderate mental retardation and hypogonadism. The disease results from mutations in the DCAF17 gene. Method: Here, we reported a large consanguineous pedigree with multiple affected individuals with Woodhouse‐Sakati syndrome phenotypes. Laboratory tests confirmed the endocrine perturbance in affected individuals. To find out the underlying genetic change, whole‐exome sequencing was carried out. Result: Analysis of the exome data identified a splicing‐site deletion NM_025000.3:c.1423‐1_1425delGACA in DCAF17 gene. Sanger sequencing confirmed the co‐segregation of the variant with the disease phenotypes in the family. Conclusion: The variant is predicted to cause aberrant splicing, i.e., exon skipping, resulting in the translation of a truncated functionless protein which results in appearance of typical phenotypic features and clinical laboratory findings of Woodhouse‐Sakati syndrome in affected members of the family. Abstract : Woodhouse‐Sakati syndrome, a rare autosomal recessive disease with endocrine and neuroectodermal abnormalities including progressive sensorineural hearing loss, alopecia, mental retardation and hypogonadism resulting from mutations in the DCAF17 gene. Here we reported a large consanguineous family with multiple affected individuals showing Woodhouse‐Sakati syndrome phenotypes and having a novel a splice site deletion mutation in DCAF17 gene